The most common reproductive disorders of cows in Holstein cattle breeding - Eva Kašná; Ludmila Zavadilová; Zuzana Krupová; Soňa Šlosárková; Petr Fleischer (Czech Journal of Animal Science, 2023)
The paper deals with the genomic evaluation of retained placenta (RP), metritis/endometritis (MET), and cystic ovarian disease (CYS) and their involvement in the selection programme of Holstein cattle. A procedure for the estimation of genetic parameters and genomic breeding values was proposed. The dataset included farmers' records of 127 000 lactations from 109 farms for RP, 185 000 lactations from 131 farms for MET and 115 000 lactations from 87 farms for CYS. The lactational incidence was 6.9% (RP), 12.8% (MET) and 9.2% (CYS). The single-trait animal model equation included fixed effects of herd-year-season of calving and parity of the cow, random direct additive genetic effect, random permanent environmental effect and residual effect. The single-step genomic prediction (ssGBLUP) was based on more than 50 000 SNP-genotyped individuals. Heritability for all traits did not exceed 2%. Favourable correlations were found between reproductive disorders resistance, fertility and longevity traits. The correlation between CYS and milk protein yield indicated a genetic predisposition to cystic ovarian disease in high-producing cows. All significant correlations between health traits (clinical mastitis, claw and feet disorders, reproductive disorders) were positive, indicating that the selection for improvement of one health trait would induce a favourable selection response in the others.